PENILAIAN TINGKAT KESEHATAN BANK SYARIAH MANDIRI: PENDEKATAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL) - Husain, Muhammad Rizky; Hikmah, Nor; Chairina, Chairina (MALIA: Journal of Islamic Banking and Finance, 2018)
The purpose of this study is to analyze the health level of Bank Syariah Mandiri in the period 2012-2016 with RGEC method. This method consists of four factors. These factors are risk profile, good corporate governanc),earning and capital. This research is a descriptive study. Data analysis unit of this research is Annual Report of Bank Syariah Mandiri in the period of 2012 until 2016, this research use quantitative data with source of secondary data and analysis method of data in this research is descriptive quantitative. The results of research show that the performance decline of Bank Syariah Mandiri in 2013 is caused by increased operating expenses exceeding the increase in operating income. The performance decline of Bank Syariah Mandiri in 2014 is caused by losses suffered by Bank Syariah Mandiri resulting from a decrease in operating income accompanied by an increase in operating expenses while the total of assets increased. However, in 2015, the level of health of BSM settled in rank 3 with the title of being quite healthy, and the level of health of BSM in 2016 increased to rank 2 with a healthy predicate.